Front Cover: Interconversion of tetrahedral [(M)4∩{Mg4(L1)6}]/[In4(L2)4] and cyclic [In6Cl6(L3)6]. Enantiotopization of diastereotopic protons monitored by means of VT 1H NMR spectroscopy (Eur. J. Inorg. Chem. 4/2022). Issue 4 (12th January 2022) - Bauer, Walter; Maid, Harald; Saalfrank, Rolf W.
Abstract : The Front Cover shows the enantiotopization of diastereotopic groups via enantiomerization using isopropyl‐COT as an example. This fundamental phenomenon is the common thread running through the manuscript. Impressively, this is also shown by the dynamic temperature dependent (VT) 1 H NMR spectrum for the diastereotopic methylene protons (green) of meso ‐[In4 (L)4 )] 1 . Because of the helitopic ligands (L) 3−, all signals are triplicated. Due to mesomerization (Bailar twist/helitopization) of the identical twins ( 2Δ, 2Λ )( 2P, 2 M )‐1 ⇌ ( 2Λ, 2Δ )( 2 M, 2P )‐1′ all signals coalesce. More information can be found in the Minireview by R. W. Saalfrank and co‐workers .